2004
DOI: 10.1002/pmic.200300741
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach to analyze salt‐responsive proteins in rice leaf sheath

Abstract: To examine the response of rice to salt stress, changes in protein expression were analyzed using a proteomic approach. To investigate dose‐ and time‐dependent responses, rice seedlings were exposed to 50, 100 and 150 mM NaCl for 6 to 48 h. Proteins were extracted from leaf sheath and separated by two‐dimensional polyacrylamide gel electrophoresis. Eight proteins showed 1‐ to 3‐fold up‐regulation in leaf sheath, in response to 50 mM NaCl for 24 h. Among these, three proteins were unidentified (LSY081, LSY262 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
157
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(164 citation statements)
references
References 35 publications
5
157
1
1
Order By: Relevance
“…Over the past years, the proteomic approach has been applied to analyze the proteins involved in various stress responses in plants, such as drought [13], salinity [14,15], and cold [10,16]. To the best of our knowledge, there are no reports, to date, addressing the identification of Al-responsive proteins from plants using proteomic approach, not even using conventional biochemical protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, the proteomic approach has been applied to analyze the proteins involved in various stress responses in plants, such as drought [13], salinity [14,15], and cold [10,16]. To the best of our knowledge, there are no reports, to date, addressing the identification of Al-responsive proteins from plants using proteomic approach, not even using conventional biochemical protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic approach has been applied to study rice responses to salt stress at seedling stage [7,[12][13][14]. The saltresponsive proteins in the roots of the salt-tolerant rice variety Pokkali and the salt-sensitive variety IR29 were studied previously [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although eight of these are known salt-stress response proteins, the majority have not been reported in the literature. In proteomic studies, the level of different SOD isoforms were found up-regulated under drought [4,49], salt [1,44], and ozone [2,15]. SOD activity, determined by multigene family, is changing under different environmental conditions.…”
Section: Proteomic Analyses Of Rice Under Drought Stressmentioning
confidence: 99%
“…Whereas four of the changed proteins had been previously identified as salt stress-responsive proteins, six were novel: UDP-glucose pyrophosphorylase, cytochrome c oxidase subunit 6b-1, glutamine synthetase root isozyme, putative nascent polypeptide-associated complex alpha chain, putative splicing factor-like protein, and putative actin-binding protein. The reports of Abbasi and Komatsu [1] and Yan et al [57], taken together, show that specific proteins that have enhanced abundances in distinct regions of the rice plant are involved in a coordinated response to salt stress. Dooki et al [12] employed a proteomic approach to further elucidate the mechanism of responses of plants to salt at an early reproductive stage.…”
Section: Proteomic Analyses Of Rice Under Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation